Complications of urologic laparoscopic surgery: A center surgeon's experience involving 601 procedures including the learning curve. Issue 5 (21st December 2012) - Akin, Yigit; Ates, Mutlu; Celik, Orcun; Ucar, Murat; Yucel, Selcuk; Erdogru, Tibet
Abstract: When indications for laparoscopy were expanded to include a variety of urologic diseases, this increased the importance of prevention of complications, especially during the surgeons' learning curve period. Therefore, we evaluated the complications of urologic laparoscopic surgery in the course of one surgeon's experience including the learning curve after completing his long‐term fellowship program. From December 2004 to August 2010, a total of 601 urologic laparoscopic surgical procedures were performed by a single surgeon who had finished a 9‐month fellowship program at an experienced center. The intra‐ and postoperative complications of these cases were documented and graded according to the modified Clavien classification system, and then compared with the first and second 3‐year periods. Of these 601 laparoscopic procedures, 47 complications occurred in 38 patients, resulting in a total complication rate of 7.8%. Conversion to open surgery occurred in four (0.6%) patients. Clavien grades I and II accounted for minor complications and occurred in 36 (5.9%) patients, whereas grades III, IV, and V accounted for major complications, which occurred in 11 (1.8%) patients. The annual complication rates formed a plateau in the 3rd year. Complication rates were significantly lower in the second 3‐year period compared with the first 3 years ( p < 0.05). Despite the well‐organized training program and transferability, surgeons must practice caution in the early years until they become more experienced. In spite of the presence of experienced laparoscopic surgeons, the surgical team needs time to gain experience. These factors cause complication rates to form a plateau in terms of time and experience.